PERANAN SELOKO DALAM UPACARA ADAT PERKAWINAN MASYARAKAT DI KOTA JAMBI - Abdoel Gafar (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2012)
This research purpose to give description about part of “seloko” contained in the tradition of wedding ceremony Jambi society as a form of preservation of local cultural elements jambi especially for “seloko”. The tradition of wedding ceremony Jambi society has eleven parts in implementation that is time to introduction, “tegak batuik duduk bertanyo”, “ulur antar serah terima adat dan lumbago”, full custom event, bribery sapat rice, “tunjuk ajar tegur sapo”, notice and pray. The role of seloko in part implementation tradition of wedding ceremony jambi society namely as a media to express feel love in stages in the association teens “berusik sirih berguau pinang”, as a partner media choice in mate selection parts, as a communication media in the part of “tegak batuik duduk bertanyo”, “ulur antar pengantin (bride)”, opening ceremonial lanse, as a media to give advice in part of “tunjuk ajar tegur sapo”, as apologize media, as information media and as media to say pray in part of notice.Keywords: implementation, “seloko”, tradition of wedding ceremony